Using structural equation modeling to examine correlations between health-related physical fitness and cell health among Chinese college students - Jian Zhu; Yi Yang; Yanmin Zhao; Guoyang Qin; Xin Su (BMC, 2024)
Abstract Introduction College students' physical fitness is likely to be directly related to their cells' health. However, there is a lack of literature on whether the relationship between cell health and college students' physical fitness is direct or indirect. This study used a structural equation modeling (SEM) approach to investigate the connection between cell health and college students' physical fitness. Methods This cross-sectional study collected data from 838 volunteers (502 males and 336 females, average age of 18.74 ± 1.5 years) who were college students from the Shandong province of China in July 2023. Initially, we obtained anthropometric measurements and conducted physical fitness tests on the students. Then, we performed Pearson correlation analysis and principal component analysis to screen variables and explore potentially influencing factors. Finally, we examined associations between the variables and determined whether there were direct or indirect influences among factors using SEM. Results The results revealed a significant correlation between the cell health factor and the muscle strength factor (path coefficient = 0.97; p < 0.001) as well as the fat obesity factor (path coefficient = -0.52; p < 0.001). The cardiovascular factor exhibited a weak correlation with the cell health factor (path coefficient = 0.11; p < 0.01). Moreover, the cardiovascular factor acted as a mediating variable between the muscle strength factor and the cell health factor, with a positive correlation observed between the muscle strength factor and the cell health factor (path coefficient = 0.40; p < 0.001). Conclusion These findings suggest that cell health is indicative of muscle strength and cardiorespiratory fitness. Our findings demonstrate that assessing the cell health of college students can be a valuable method for evaluating their overall health.